Currency Board Versus Central Bank in a Currency Crisis - Ho, Kenneth Tat Meng (1998)
From June 1997 till presently had been a period of economic turmoil for many parts of the Asian region. There has been experiences of economic overheating, inflation, deficit balance of payments, rising interest rate s coupled with the downward spiral of the stock market s and currency devaluations. This has brought about numerous debates on the causes and remedies of this crisis. Among them are the usefulness of the currency board regime in regulating the exchange rate s of the countries involved. This is an alternative system to the present regime of central bank s in managing the countries' money supply. The currency board basically is a monetary regime whereby the exchange rate of the country as fixed with a chosen anchor currency whereby all its money supply must be 100% backed by its foreign reserves. The central bank system employs the floating exchange rate which has been unsuccessful in warding off speculations on the currency. Further many other disadvantages will be discussed in this thesis. This thesis discuss the comparative characteristics between the currency board and the central bank monetary regime in all its advantages and disadvantages. An attempt i s made to define the currency board and the central bank and the many versions associated with them. (Le., classical, modern and AEL-Argentina, Lithuania, Estonia -model) A closely related concept to the currency board, namely dollarization is also discussed.